Optimum utilisation of altitude training - the high-low model - Kearney, J.; Wilber, R. (1998)
R. Chapman speakes about the haematological, pharmacological, environmental and structural adaptations at altitude training. The theories behind the live-high-train-high and the live-high-train-low-modell are explained. A prescription for altitude training is given.